Research Methodology for the Maintains Education Sector Study in Uganda - Brown, Victoria; Kyeyune, Robinah; Kibombo, Richard; Hudda, Nabil; Ruddle, Nicola (Oxford Policy Management, Oxford, 2020)
Since violence first broke out in South Sudan in December 2013 there has been continued violence and a mass influx of refugees into Uganda. Uganda is the largest refugee-hosting country in Africa, with 1.19 million refugees in December 2018, most of whom have fled from the crises in Burundi, the Democratic Republic of the Congo, and South Sudan. Refugees are located in 12 districts. Roughly 66% of refugees are from South Sudan, 26% from the Democratic Republic of Congo, and 3% from Burundi (United Nations High Commissioner for Refugees (UNHCR), 2019).The country has a long history of welcoming refugees within its borders, and is known for its pro-refugee policies, allowing refugees to settle among the local population and to share land and access basic services.
Keywords: Study; Research Methodology; Maintains